Kajian QS. Al-Baqoroh Ayat 224 dalam Tafsir Al-Qurthubi: Memahami Makna Sumpah yang Terlarang - Athya, Mayada (Al-Kauniyah : Jurnal Ilmu Alquran dan Tafsir, 2024)
Oaths in general can be considered as something that has a very sacred meaning. The oaths that can be found in this data are very diverse, starting from oaths that include the name of God, the family name, the name of a tribe or a custom followed, and things that are considered valuable or other important. In practice in society, an oath is simply understood as a reinforcing statement or statement which, when spoken, means that what is said afterwards is true, then regarding the permissibility of this oath itself, of course there are differences in how to respond to it. Therefore, to determine the right attitude or opinion, it must be based on laws that are universal and have absolute truth. The basis of this law is the Koran. In responding to life and all its problems, the Qur'an always has answers that must be understood, studied and studied correctly and precisely so as not to give rise to opinions or beliefs that are not appropriate. One of the verses in the Koran that discusses oaths is QS. al-Baqoroh verse 224. In this article we will discuss how the interpretation views this verse and the law of the oath itself.